2017
DOI: 10.3389/fphar.2017.00416
|View full text |Cite
|
Sign up to set email alerts
|

Observed and Normative Discount Functions in Addiction and other Diseases

Abstract: The aim of this paper is to find a suitable discount function able to describe the progression of a certain addiction or disease under treatment as a discounting process. In effect, a certain indicator related to a disease decays over time in a manner which is mathematically similar to the way in which discounting has been modeled. We analyze the discount functions observed in experiments which study addictive and other problematic behaviors as well as some alternative hyperbola-like discount functions in orde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Therefore, impatience could be an early indication of a problem of self-control which could result in overweigh, obesity or even other diseases (e.g., addiction), given that excessive discounting may be considered as a trans-disease process ( 40 , 41 ). This finding could be used to identify the target population where policy interventions are needed in order to promote healthier diet habits.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, impatience could be an early indication of a problem of self-control which could result in overweigh, obesity or even other diseases (e.g., addiction), given that excessive discounting may be considered as a trans-disease process ( 40 , 41 ). This finding could be used to identify the target population where policy interventions are needed in order to promote healthier diet habits.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, smokers value the pleasure they receive from smoking in the present whilst heavily discounting the negative consequences of smoking in the future ( 20 ). Besides hyperbolic discounting, several studies modeled time-inconsistent addictive behavior by the exponentiated hyperbolic discounting ( 28 ) and subadditive discounting ( 29 , 30 ). In addition to time-inconsistency, smokers, particularly young smokers, are often found to have imperfect information; they lack judgment in understanding future health consequences and sometimes become addicted suddenly ( 31 35 ).…”
Section: Introductionmentioning
confidence: 99%
“…Internet addiction has been known to be linked to a host of negative outcomes for those who are addicted to internet (Koronczai et al, 2011), such as reduced work efficiency (Anandarajan et al, 2000), lowered academic achievement and social relationship (Young, 1996;Young et al, 1999;Cash et al, 2012), increased abnormal behaviors and behavioral disorders (Lam et al, 2009;Lin et al, 2011;Li et al, 2016Li et al, , 2019, and neurological dysfunction (Dalbudak et al, 2014;Petry et al, 2014Petry et al, , 2018. Studies have indicated that short-sighted decision making is related to cognitive function impairment among individuals with addictive disorders (Hare et al, 2009;Levitt et al, 2010;Cruz Rambaud et al, 2017;Calluso et al, 2020). Moreover, previous studies found that there is a significantly negative correlation between working memory and delay discounting rates (Hinson et al, 2003;Shamosh et al, 2008).…”
Section: Introductionmentioning
confidence: 99%